2013
DOI: 10.1016/j.aim.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary and symbolic powers are Golod

Abstract: Let S be a positively graded polynomial ring over a field of characteristic 0, and I ⊂ S a proper graded ideal. In this note it is shown that S/I is Golod if ∂(I) 2 ⊂ I. Here ∂(I) denotes the ideal generated by all the partial derivatives of elements of I. We apply this result to find large classes of Golod ideals, including powers, symbolic powers, and saturations of ideals.2000 Mathematics Subject Classification. 13A02, 13D40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…, x m ] is a polynomial ring over k (where m ≥ 0) and (0) = I ⊆ R is a proper homogeneous ideal. Following Herzog and Huneke [31], if char k = 0 we say that a homogeneous (but possibly non-monomial) ideal I is strongly Golod if ∂(I) 2 ⊆ I. Independently of char k, we say that an ideal I is * strongly Golod if I is a monomial ideal and ∂ * (I) 2 ⊆ I.…”
Section: 2mentioning
confidence: 99%
“…, x m ] is a polynomial ring over k (where m ≥ 0) and (0) = I ⊆ R is a proper homogeneous ideal. Following Herzog and Huneke [31], if char k = 0 we say that a homogeneous (but possibly non-monomial) ideal I is strongly Golod if ∂(I) 2 ⊆ I. Independently of char k, we say that an ideal I is * strongly Golod if I is a monomial ideal and ∂ * (I) 2 ⊆ I.…”
Section: 2mentioning
confidence: 99%
“…As a first application we prove a result analogue to [8,Theorem 2.3], whose proof follows very much the line of arguments given there. The new and important fact is that no assumptions on the characteristic of the base field are made.…”
Section: Applicationsmentioning
confidence: 71%
“…On the other hand, if char(K) = 0 and I is a monomial ideal, then I is strongly Golod in the sense of [8] if and only if it is strongly d-Golod. This follows from the remarks at the begin of Section 3 in [8], where it is observed that a monomial ideal I is strongly Golod if and only if for all monomial generators u, v ∈ I and all integers i and j with x i |u and x j |v it follows that uv/x i x j ∈ I. Indeed, it is obvious that strongly Golod implies strongly d-Golod.…”
Section: A Golod Criterionmentioning
confidence: 99%
“…, x n ] and s ≥ 2. Herzog and Huneke [22] proved recently that any such R is a Golod ring, in particular any finitely generated graded module over R has rational Poincaré series.…”
Section: Introductionmentioning
confidence: 99%